Nonlinear viscous damping and tuned mass damper design for occupant comfort in flexible tall buldings sinjected to wind loading - Inaudi, José A. (2017)
Fil: Inaudi, José A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Departamento de Aeronáutica; Argentina.